F; Quality Control Analysis on 1.5 Tesla MRI Aircraft at the Radiology Installation of Sanjiwani Hospital - Ida Bagus Candra Prabhawa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Magnetic Resonance Imaging (MRI) is a medical imaging modality that is capable of producing high-resolution anatomical images without the use of ionizing radiation. The quality of MRI images is greatly influenced by the stability of the system and the performance of the hardware, therefore, the implementation of routine Quality Control (QC) is essential to ensure patient safety and diagnostic accuracy. Imaging artifacts are frequent and can reduce image quality as well as interfere with clinical interpretation. In regional hospitals with limited availability of standard ACR phanthoms, visual checklist assessment and artefact evaluation are commonly used as practical QC methods. This study aims to analyze the implementation of Quality Control on the 1.5 Tesla MRI system at the Radiology Installation of Sanjiwani Hospital, focusing on the application of visual checklist and artifact evaluation assessments. This study uses a qualitative design with a survey approach conducted from February to March 2026. Data were collected through direct observation, visual checklist assessment, and documentation of phantom imagery results. Data analysis was carried out descriptively. The results showed that all parameters on the visual checklist for 30 days were in good condition and the entire MRI system was able to function normally without any equipment interference. The results of the artifact evaluation conducted on February 26, 2026, March 5, 2026, March 12, 2026, and March 19, 2026 also show the absence of artifacts on the MRI images. Based on the 2015 ACR standard, the results were characterized by a phantom image that appeared circular, homogeneous, symmetrical, there were no ghost images, no abnormal shadows, and no image distortion was found. Conditions in the field show that the implementation of QC at Sanjiwani Hospital still uses simple methods in the form of visual checklists and artifact evaluations, but is still able to monitor the stability of the MRI system regularly. The conclusion of this study shows that the 1.5 Tesla MRI aircraft at Sanjiwani Hospital is still operating well and has met MRI Quality Control standards based on the 2015 ACR guidelines. Regular implementation of QC through visual checklists and artifact evaluation can help maintain system stability and MRI image quality to support diagnostic services.